You need to move all terms that contain x to one side such that:

`x^2 - 6x = 0 `

Notice that both terms have a common factor x, hence, factoring out x yields:

`x(x - 6) = 0`

Since a product of two factors is 0 when a factor or...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to move all terms that contain x to one side such that:

`x^2 - 6x = 0 `

Notice that both terms have a common factor x, hence, factoring out x yields:

`x(x - 6) = 0`

Since a product of two factors is 0 when a factor or both are zeroes, hence, you need to set the following equations such that:

`{(x=0),(x-6=0):} =gt {(x=0),(x=6):}`

**Hence, evaluating the solution to the given equation using factorization, yields `x = 0` and `x = 6.` `.` **